2008
DOI: 10.1002/app.28465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Hindered Amine Stabilizer (HAS) on radiolytic and thermal stability of poly(methyl methacrylate)

Abstract: Commercial Poly(methyl methacrylate) (PMMA) containing Tinuvin 622, a Hindered Amine Stabilizer (HAS), in 0.3% (wt/wt) concentration was investigated. The samples were irradiated with gamma radiation ( 60 Co) at room temperature in air. The viscosity-average molecular weight (M v ) was analyzed by viscosity technique. Both control PMMA (without HAS) and PMMA 1 622 (with HAS) showed a decrease in molecular weight with the increase in dose, reflecting the random scissions that occurred in the main chain. The G v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…These results suggest that PMMA‐control undergoes more thermal degradation in industrial process than PMMA‐622. In addition, the activation energy calculated for thermal degradation of PMMA was 165 kJ/mol, this activation energy increased 60 kJ/mol when Tinuvin 622 was added to PMMA matrix 18. Thus, the PMMA‐622 samples are more thermally stable than PMMA‐control.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These results suggest that PMMA‐control undergoes more thermal degradation in industrial process than PMMA‐622. In addition, the activation energy calculated for thermal degradation of PMMA was 165 kJ/mol, this activation energy increased 60 kJ/mol when Tinuvin 622 was added to PMMA matrix 18. Thus, the PMMA‐622 samples are more thermally stable than PMMA‐control.…”
Section: Resultsmentioning
confidence: 96%
“…Note that M v decreases continuously with increase of absorbed dose due main chain scission effect. In our previous work,18 we calculated the G values (scission/100 eV) of 2.6 for PMMA‐control and 1.0 for PMMA‐622 at dose range of 0–60 kGy. These results represent 61% of reduction in yield of chain scission in PMMA matrix by Tinuvin 622 action.…”
Section: Resultsmentioning
confidence: 99%
“…Ours previously study 15 showed that the PMMA in study contains a double bond in the end group, which is formed through radical polymerization of PMMA 34,35 . In general, under inert atmosphere, thermal degradation of double bond-terminated PMMA (PMMA=) prepared by radical polymerization exhibits four main weight losses events, corresponding to four degradation stages 34,35,36 .…”
Section: Thermogravimetric Analysis Of Pmma/pbs-np Filmsmentioning
confidence: 96%
“…In general, under inert atmosphere, thermal degradation of double bond-terminated PMMA (PMMA=) prepared by radical polymerization exhibits four main weight losses events, corresponding to four degradation stages 34,35,36 . The first stage corresponds to the degradation initiated by radical transfer to the unsaturated chain end; the second and third stages result from the homolytic scission of the chain due to headto-head bonds and degradation initiated by radical transfer to the unsaturated chain end; the fourth stage corresponds to random scissions 15 . TGA thermograms of PMMA and PMMA/PbS-NP (0.3 wt%) are shown in Figure 7a for unirradiated systems.…”
Section: Thermogravimetric Analysis Of Pmma/pbs-np Filmsmentioning
confidence: 99%
See 1 more Smart Citation